Sacrospinous ligament suspension with transobturator mesh versus sacral colpopexy for genital prolapse (Clinics, 2016)
OBJECTIVE: To compare the safety and efficacy of abdominal sacral colpopexy and sacrospinous ligament suspension with the use of vaginal mesh for apical prolapse. METHOD: This retrospective study was conducted from 2005 to 2012 and included 89 women with apical prolapse who underwent surgery. Assessments included pre- and postoperative Pelvic Organ Prolapse Quantification (POP-Q) stage. Rates of objective cure and immediate/late complications were compared. RESULTS: In total, 41 of the 89 women underwent sacrospinous ligament suspension, and 48 of the women underwent abdominal sacral colpopexy. A total of 40.4% of the women had vault prolapse (p=0.9361). Most of them had no complications (93.2%) (p=0.9418). Approximately 30% of the women had late complications; local pain was the main symptom and was found only in women who underwent the abdominal procedure (25.6%) (p=0.001). Only the women who were submitted to the vaginal procedure had mesh exposure (18.4%). The objective success rate and the rate of anterior vaginal prolapse (p=0.2970) were similar for both techniques. CONCLUSION: Sacrospinous ligament suspension was as effective and had a similar objective success rate as abdominal sacral colpopexy for the treatment of apical prolapse. Sacrospinous ligament suspension performed with the use of vaginal mesh in the anterior compartment was effective in preventing anterior vaginal prolapse after surgery.